Knowledge, Attitude and Perceptions of Healthcare Workers in Arab Countries Regarding Basic Life Support; a Systematic Review and Meta-Analysis - Mohammed Alsabri Hussein Alsabri; Sarah Makram Elsayed; Basel Faird; Alaa Ahmed Elshanbary; Mohamed Sayed Zaazouee; Alishah Zehra (Archives of Academic Emergency Medicine, 2024)
Introduction: Effective Basic Life Support (BLS) interventions, including cardiopulmonary resuscitation (CPR), are essential for enhancing survival rates. This review aimed to evaluate the knowledge, attitudes, and perceptions (KAP) of healthcare professionals regarding BLS in Arab countries.